Pemanfaatan Media Pembelajaran Digital Sebagai Upaya Pembiasaan Literasi Siswa Sekolah Dasar - Siti Auliakhasanah; Wanda Hamidah; Widia Triyana; Azzahra Elisa Putri; Sofyan Iskandar; Nuur Wachid Abdulmajid; Neneng Sri Wulan (FKIP, Universitas Palangka Raya, 2023)
Reading and writing literacy needs to be developed as the main skill to achieve other skills. The results of this study aim to sort out learning media that are valid, effective, innovative, flexible, and efficient. The type of research used in this study is qualitative using descriptive analysis methods. This research was carried out by interviewing 1 informant from one of the elementary schools, as well as filling out a questionnaire/questionnaire with 6 respondents. Based on the information obtained through interviews and filling out questionnaires/questions, elementary schools have involved the use of technology/digital media in learning activities and literacy programs which are being intensified by the government. With the existence of digital learning media students can access reading books easily, so that the role of this learning media can significantly influence student independence in reading literacy activities.